A STUDY OF ALUMNI FEEDBACK ON PEDAGOGICAL CURRICULUM EVALUATION - Devinta Puspita Ratri; Dian Novita Dewi; Yulia Hapsari (Erudio Journal of Educational Innovation, 2019)
This study was aimed at investigating the need of alumni on the pedagogical knowledge and skills in their job as teachers and how sufficient the pedagogical courses offered at ELEP are in meeting the need of the alumni to do their job as teachers. To reach the objective of the study, survey method with cross-sectional design was employed. A set of questionnaire adapted from Tanriverdi & Apak (2013) study pertinent to pedagogical courses was distributed to alumni who are working as teachers. Responses from the questionnaires were analyzed to reveal the need of the alumni on the pedagogical knowledge and skill. Results of the analysis were further used to as a consideration to carefully select informants for an interview. From all the data collected and analyses conducted, it can be concluded that most pedagogical courses offered in ELEP are needed. However, few are in need refining that more practical knowledge is more accommodated so that the students can get clearer picture of the implementation in real teaching process. As for the sufficiency, the materials given in the pedagogical courses are relatively sufficient in equipping alumni doing their job as teachers.